2021
DOI: 10.1016/j.jaip.2021.06.010
|View full text |Cite
|
Sign up to set email alerts
|

First-Dose mRNA COVID-19 Vaccine Allergic Reactions: Limited Role for Excipient Skin Testing

Abstract: Background CDC states that a severe or immediate allergic reaction to the first dose of an mRNA COVID-19 vaccine is a contraindication for the second dose. Objective To assess outcomes associated with excipient skin testing after a reported allergic reaction to mRNA COVID-19 vaccine dose one. Methods We identified a consecutive sample of patients with reported allergic reactions after the first dose of mRNA COVID-19 vaccine who underwent alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
141
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(152 citation statements)
references
References 28 publications
9
141
0
2
Order By: Relevance
“…A careful allergology personal history appears the most important moment, which should not be limited to the evaluation of known vaccine excipient sensitization. Skin testing before vaccine dose two administration was not predictive in a recent study, with negative skin tests in patients who developed reactions to their 388 mRNA COVID-19 vaccine second dose [5]. In our experience, the personal allergy history was positive for penicillin and other drug reactions, instead of the allergens considered related to the messenger RNA (mRNA) vaccine, such as polyethylene glycol, polyoxyl castor oil, or polysorbate.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…A careful allergology personal history appears the most important moment, which should not be limited to the evaluation of known vaccine excipient sensitization. Skin testing before vaccine dose two administration was not predictive in a recent study, with negative skin tests in patients who developed reactions to their 388 mRNA COVID-19 vaccine second dose [5]. In our experience, the personal allergy history was positive for penicillin and other drug reactions, instead of the allergens considered related to the messenger RNA (mRNA) vaccine, such as polyethylene glycol, polyoxyl castor oil, or polysorbate.…”
Section: Discussionmentioning
confidence: 53%
“…A careful allergology personal history appears the most important moment, which should not be limited to the evaluation of known vaccine excipient sensitization. Skin testing before vaccine dose two administration was not predictive in a recent study, with negative skin tests in patients who developed reactions to their 388 mRNA COVID-19 vaccine second dose [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many cases of successful revaccination of the second dose with the same platform after experiencing an immediate hypersensitivity reaction to the first dose have been reported. [17][18][19][20][21] We provide the recommendation for individuals with anaphylactic reactions to the CoronaVac COVID19 vaccine, summarized in Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…Two academic allergy groups have begun evaluation of the Boston HCW who reported allergic symptoms within 3 days of vaccination for evidence of allergic sensitization. Wolfson et al [ 40 ] have reported the results of testing the first 80 individuals for HMW PEG allergy by skin testing and reported outcomes of repeat vaccine dosing. Skin testing to PEG 3350 was used as a surrogate for the PEG 2000 incorporated into the LNP of the mRNA vaccines.…”
Section: Allergy Testing and Repeat Vaccination In Adults Suffering Immediate Allergic Reactions (<4 Hours) After Covid-19 Mrna Vaccinatimentioning
confidence: 99%